Handbook of nanotechnology applications : environment, energy, agriculture and medicine - Faungnawakij, Kajornsak; Lau, Woei Jye; Ruktanonchai, Uracha Rungsardthong; Piyachomkwan, Kuakoon (Micro and nano technologies, 2021)
Handbook of Nanotechnology Applications: Environment, Energy, Agriculture and Medicine presents a comprehensive overview on recent developments and prospects surrounding nanotechnology use in water/wastewater separation and purification, energy storage and conversion, agricultural and food process, and effective diagnoses and treatments in medical fields. The book includes detailed overviews of nanotechnology, including nanofiltration membrane for water/wastewater treatment, nanomedicine and nanosensor development for medical implementation, advanced nanomaterials of different structural dimensions (0D, 1D, 2D and 3D) for energy applications, as well as food and agricultural utilization. Other sections discuss the challenges of lab-based research transitioning towards practical industrial use.